Review of NVP and HG and Early Pharmacotherapeutic Intervention. (24th November 2011) - Clark, Shannon M.; Costantine, Maged M.; Hankins, Gary D. V.
Abstract : NVP occurs in 50–90% of pregnancies, making it a common medical condition in pregnancy. Women present differently with any combination of signs and symptoms. It is appropriate to take the pregnancy-related versus nonpregnancy-related approach when determining the cause of nausea and vomiting but other causes should be considered. The most common etiologies for NVP include the hormonal changes associated with pregnancy, the physiologic changes in the gastrointestinal tract, and a genetic predisposition. Up to 10% of women will require pharmacotherapy to treat the symptoms of NVP despite conservative measures. ACOG currently recommends that a combination of oral pyridoxine hydrochloride and doxylamine succinate be used as first-line treatment for NVP if pyridoxine monotherapy does not relieve symptoms. A review of NVP and early pharmacotherapeutic management is presented due to the fact that NVP is largely undertreated, and investigations into the safe and effective pharmacotherapies available to treat NVP are lacking.